Review of the results from the NUCLEON space mission. Issue 5 (1st September 2022) - Podorozhny, D.; Grebenyuk, V.; Karmanov, D.; Kovalev, I.; Kudryashov, I.; Kurganov, A.; Merkin, M.; Panov, A.; Tkachev, L.; Turundaevskiy, A.; Vasiliev, O.; Voronin, A.
Abstract: The NUCLEON space observatory was developed to measure the spectra of cosmic ray nuclei with individual charge resolution in the energy range of several TeV to 1 PeV per particle. This work is a brief review of the results from the NUCLEON observatory over three years of operation in orbit. The spectra of the main primary abundant nuclei and secondary nuclei of cosmic rays (CRs) are presented. Some new interesting features of the CR spectra found in the NUCLEON data are discussed.